Adults learners in secondary schools : perceptions of the value of education held by adult learners who returned to secondary schools in the Herschel district of the Transkei - Asiamah, Samuel (My University, 2016)
This study is about adult learners in formal secondary schools attending normal day classes with school pupils. Ii is particularly about the aspirations of 1,430 adult pupils. these adults, after a break in their formal education, return to study in the secondary schools in the Herschel district of Transkei in the 1993 academic year.
Keywords: Adult education--South Africa--Transkei; Adult learning--South Africa--Transkei; Education, Secondary--South Africa--Transkei